Analysis of some engineering properties of mortars containing steel scale using Taguchi based grey method - Kelestemur, Oguzhan; Arici, Erdinc (Elsevier, 2020)
Solid wastes generated from industrial sources are continues to increase at an alarming rate. One of these industrial wastes is steel scale. In this study, relationship between the wear resistance, compressive strength and ultrasonic pulse velocity value of mortar samples produced by substituting river sand with steel scale waste was examined. For this purpose, mortar specimens with different levels of fine scale (0%, 5%, 10%, 15%), coarse scale (0%, 5%, 10%, 15%), water/cement ratio (0.5, 0.6) and cement dosage (400 kg/m(3), 500 kg/m(3)) were produced. The wear resistance, compressive strength and ultrasonic pulse velocity experiments were performed on specimens produced. Taguchi based grey relational analysis method was used to obtain optimal parameter levels for simultaneously achieving the desired properties of the mortars. L-16 (4(2) x 2(2)) orthogonal array table was used for the tests in line with the Taguchi quality design concept. Analysis of variance (ANOVA) method was used for the determination of statistically effects of the parameters on the tests. Finally, experimental results were compared with the statistical data and it was concluded that there was a good fit between them.
Keywords: Mortar; Steel scale waste; Wear resistance; Taguchi based grey method; Optimization